PERAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENGENTASKAN KEMISKINAN PERKOTAAN (STUDI KASUS PADA KOMUNITAS PUNK DI KOTA YOGYAKARTA) - Rila Setyaningsih (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
The  purpose  of  writing  this  article  is  to  describe:  (1)  Background  punk  community,  and  (2)  the  roles  of technology, information, and communication  to alleviating the urban poverty of punk. The approach used in the study  is  a  qualitative  deskripstif.  The  research  location  is  in  the  city  of  Yogyakarta.  While,  the  study  subjects were  punks  who  come  from  disadvantaged  backgrounds.  Data  collection  techniques  consisting  of:  (1) observation, (2) in-depth interviews, and (3) documentation. Analysis: (1) induction  when in the field with the pattern  of  triangulation,  (2)  a  holistic  do  after  field.  The  results  showed  that:  First,  poverty  can  be  the background of a person chooses to be a punk. Second, the role of technology, information, and communication is essential in alleviating the urban poverty, especially punk community in the city of  Yogyakarta. Keywords: Technology information and communication, Urban poverty, Punk